Optical engineering fundamentals - Walker, Bruce H. (SPIE, 2008)
This classic Tutorial Text provides a basic understanding of many fundamental optical principles. The Second Edition has been updated to reflect the development of electronic sensors, as well as the advent of mainstream consumer optical products. Chapters also emphasize the application of state-of-the-art computer software to generate solutions to related lens design and optimization problems. This is an ideal textbook for introductory courses at advanced high school and college levels. For those who proceed to work in the field of optical engineering, this book will provide a convenient source of valuable, basic reference material.
"SPIE digital library."
Title from PDF t.p. (viewed 8/23/09).
Keywords: Optics.; Optical instruments.; Lenses.; elektronické knihy; electronic books